Surgical outcomes of tethered cord syndrome in adults versus pediatric patients: A comparative study - Dinesh Shukla,; Hari Prakash Rai,; Shivam Sharma, (Asian Journal of Medical Sciences, 2025)
Background: Tethered cord syndrome (TCS) is a neurological disorder caused by the abnormal attachment of the spinal cord, which limits movement and leads to progressive neurological deficits. This study compares the surgical outcomes of TCS in pediatric and adult patients following detethering surgery at Maharani Laxmi Bai Medical College, Jhansi, Uttar Pradesh, between August 2015 and August 2024. Aims and Objectives: The aim of the study was to assess and compare the surgical outcomes, complication rates, and long-term prognosis in pediatric and adult TCS patients, with a focus on neurological improvement, post-operative complications, and quality of life. Materials and Methods: A retrospective cohort study was conducted, including 120 patients (60 pediatric and 60 adult) who underwent surgical detethering. Data were collected on patient demographics, presenting symptoms, surgical details, and post-operative outcomes. The primary outcomes were neurological improvement and functional independence. Secondary outcomes included complication rates and quality of life, assessed over a 2–5-year follow-up period. Results: Pediatric patients had significantly better neurological recovery (improvement in 70% vs. 45% of adults, P=0.014) and fewer complications (15% vs. 32%, P=0.045) compared to adults. Pediatric patients had lower re-tethering rates (10% vs. 18%, P=0.132) and higher functional independence (Glasgow outcome scale ≥4: 90% vs. 60%, P<0.001). Quality of life scores were significantly higher in pediatric patients (SF-36 score: 85.2±10.6 vs. 72.3±12.8, P=0.021). Conclusion: Pediatric patients exhibit better surgical outcomes, including higher rates of neurological improvement and fewer complications. Early diagnosis and timely surgical intervention are critical for optimizing outcomes, especially in pediatric patients.